(untitled) (Research, Society and Development, 2023)
Therapeutic ozone is a mixture of oxygen (O2) and ozone (O3) that can be produced in ozone generators and has several modalities of administration, such as minimally invasive treatment in the reduction of muscle pain and in the treatment of patients with temporomandibular disorder (TMD). This bibliographic research aimed to study the efficacy of ozone therapy in the treatment of temporomandibular disorders. This was a literature review study with a narrative approach, using the databases Latin American and Caribbean Literature in Health Sciences (LILACS), International Literature in Health Sciences (MEDLINE), US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO). The descriptors "temporomandibular joint dysfunction syndrome", "ozone" and "ozone therapy" were used. We included clinical, descriptive, quantitative, qualitative studies and complete case reports that addressed ozone therapy in the treatment of TMDs in the languages Portuguese, English and Spanish, in the period from 2012 to 2023, excluding dissertations, theses, editorials, incomplete studies and that were not related to the researched theme. The selected studies showed promising and satisfactory results in ozone therapy, whether used alone or in combination with conventional therapy. Although there is a need for more research in the literature, ozone therapy demonstrates many benefits, reducing symptoms of pain and fatigue associated with TMD and improving mandibular function, being a minimally invasive and effective therapeutic method for the treatment of TMD patients.